Blind faith or hard evidence? Exploring the indirect performance impact of design thinking practices in R&D. (20th January 2022) - Robbins, Peter; Fu, Na
Abstract : Design thinking has recently been the subject of considerable attention from academics and practitioners. In management discourse, design thinking is a creative and human‐centred problem‐solving approach based on designers' practices, used mainly in the pursuit of product, service and process innovation. Despite being increasingly promoted and adopted as an approach to innovation, we know little about whether and how design thinking influences firm performance. Drawing upon the resource‐based view of the firm and dynamic capability theory, this paper answers these questions via a two‐study approach in the context of R&D. Study 1 explores the perceived performance impact of design thinking in a descriptive way. Study 2 investigates the mediating role of organizational innovative capability in design thinking and organizational innovative performance relationship. The results from these two studies shed light on design thinking's performance impact. In addition, they add evidentiary support to the contention that design‐thinking practices applied in R&D help develop organizational innovative capability, which in turn increases organizational innovative performance. This research adds welcome evidentiary support to the contention that design thinking practices, applied in R&D, help develop organizational innovative capability, which in turn increases organizational innovative performance. Our study offers a theory‐based and actionable approach which explains the underlying mechanism through which a firm can boost its innovation performance by the adoption of design thinking.